Heritage Education and Livelihood Satisfaction in Indian Rural Communities: Towards Sustainable Development - Narmadha Velu; A. Anuradha (Qubahan Academic Journal)
Indian rural tourism is expanding as visitors discover more about the rich heritage, customs and lifestyles of rural host communities. The study is performed on a randomly selected sample of 874 persons residing in rural parts of South India. To analyze the effects of the suggested model that aims to assess the livelihood satisfaction of rural people by examining the repercussions of heritage education on their quality of life, Structural equation modelling (SEM) is employed. The results of the SEM demonstrate that factors affecting quality of life are essential in promoting livelihood satisfaction among people living in rural areas. Additionally, it is discovered that heritage education is also found to moderate the association between quality-of-life aspects and livelihood satisfaction of rural host communities. The findings reveal that rural tourism planners must go beyond methods to accomplish tourism and community development by offering Sustainable Development Goals (SDGs) by improving the livelihood satisfaction of rural host communities through heritage education. Heritage education shows the customs and authenticity of rural host communities by improving the model. The study also sheds light on implications towards the well-being of rural people through heritage education.